2011
DOI: 10.1073/pnas.1108444108
|View full text |Cite
|
Sign up to set email alerts
|

An ATP-binding cassette subfamily G full transporter is essential for the retention of leaf water in both wild barley and rice

Abstract: Land plants have developed a cuticle preventing uncontrolled water loss. Here we report that an ATP-binding cassette (ABC) subfamily G (ABCG) full transporter is required for leaf water conservation in both wild barley and rice. A spontaneous mutation, eibi1.b , in wild barley has a low capacity to retain leaf water, a phenotype associated with reduced cutin deposition and a thin cuticle. Map-based cloning revealed that Eibi1 encodes an HvABCG31 full transporter.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 52 publications
(71 reference statements)
2
112
0
1
Order By: Relevance
“…First, the mechanism of intracellular and extracellular transport of wax and cutin precursors remains unknown, although key ABC transporters required for their export across the plasma membrane have been identified (Pighin et al, 2004;Bird et al, 2007;Chen et al, 2011). The first cutin synthase has been identified (Girard et al, 2012;Yeats et al, 2012b), but there are certainly additional cutin synthases, and whether they are closely related to CD1 or belong to distinct protein families remains to be discovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the mechanism of intracellular and extracellular transport of wax and cutin precursors remains unknown, although key ABC transporters required for their export across the plasma membrane have been identified (Pighin et al, 2004;Bird et al, 2007;Chen et al, 2011). The first cutin synthase has been identified (Girard et al, 2012;Yeats et al, 2012b), but there are certainly additional cutin synthases, and whether they are closely related to CD1 or belong to distinct protein families remains to be discovered.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, full transporters required for cutin deposition were identified in Arabidopsis (ABCG32; Bessire et al, 2011) as well as wild barley (Hordeum spontaneum) and rice (Oryza sativa; Chen et al, 2011). Despite the clear genetic evidence supporting a role for ABC transporters in cuticular lipid export, the substrate specificity of these transporters has not yet been demonstrated in vitro.…”
Section: Transport Of Cuticle Precursorsmentioning
confidence: 99%
“…However, it is possible that Lr34sus-D, Lr34-B, OsABCG50 and the two sorghum orthologs have conserved functions. For example, two recent studies identified three orthologous ABCG transporters from barley, rice and Arabidopsis that are all involved in the formation of cutin layers (Bessire et al 2011;Chen et al 2011).…”
Section: Lr34 Haplotypes In Wheat Rice and Sorghummentioning
confidence: 99%
“…In addition to the ABCG clade of half transporters, full-size ABCG transporters of the PLEIOTROPIC DRUG RESISTANCE (PDR) family have been implicated in cuticular lipid export following characterization of the pec1 mutant of Arabidopsis and the eibi mutant of barley, which have been designated PEC1/AtABCG32 and Hv-ABCG31, respectively (Bessire et al, 2011;Chen et al, 2011a). Interestingly, the AtABCG32 transporter is highly conserved between monocots and dicots, exhibiting 70% amino acid identity between Arabidopsis and rice.…”
Section: Abcg Transporters Of the Pdr Familymentioning
confidence: 99%